Strategy Development for the Turkish Ready-Made Garment Sector Using SWOT Analysis - Fuzzy TOPSIS Method - (:unkn) unknown (INST CHEMICAL FIBRES, 2020)
The aim of this study was to integrate SWOT analysis and the fuzzy TOPSIS method to develop a strategy for the Turkish RMG sector. SWOT analysis was used to determine the strengths & weaknesses and opportunities & threats of the sector. New strategies were developed using SWOT analysis data, and then the fizzy TOPSIS method was used to rank the strategies for the sector. Four strategies were determined: (1) building global brands, (2) providing government incentives to increase the competitive power of the sector (3) effective use of e-commerce, and (4) transforming the sector into an attractive business area for young people. Empirical results indicate that the third strategy is ideal for the sector. However SWOT analysis falls short of determining strategies for any sector. The ability of strategy making processes to yield positive outcomes depends largely on managers' participation in decision-making processes. Fuzzy TOPSIS was used to model the inherent uncertainty in human knowledge and behaviour and to incorporate sector managers 'views into the .system to assess alternatives that integrate SWOT.
Keywords: RMG sector; strategy development; SWOT analysis; fuzzy TOPSIS; INDUSTRY